REVIEW: EKSTRAKSI, IDENTIFIKASI, KUANTIFIKASI ALKALOID KININ DARI KULIT BATANG KINA (Cinchona succirubra Cortex) - Gusti Agung Ayu Made Dwi Khania Adysti (Jurnal Ilmiah Kedokteran dan Kesehatan, 2023)
One of the plants used for medicinal purposes is quinine, especially the bark part containing quinine alkaloids. Extraction by Soxhlet method and identification of groups by phytochemical screening method. Fractures by liquid-liquid extraction methods, thin-layer chromatography, and slow column chromatography. Isolate by the preparative chromatography method and the KLT-Densitometry method. The extraction by Soxhlet's method was obtained with a reddish-brown extract. The phytochemical screening results are positive for alkaloids and triterpenoids. Liquid extraction results in water fractions, ethyl acetate I fractions and ethyl acetate II fractions. KLT results and chemical reagent identification obtained replication fraction I and replication II containing kinin. Using the KLT Densitometry method, it is shown that the quinine stem skin extract positively contains a kinin compound with an average kinin content of 15.30%.